Location of the Transcription Defect in Group I Temperature-Sensitive Mutants of Vesicular Stomatitis Virus - Hunt, D. Margaret (1974)
The ribonucleoprotein-dependent RNA transcriptase in vesicular stomatitis B virions of four temperature-sensitive (ts) mutants belonging to complementation group I was analyzed in vitro at permissive (31 C) and restrictive (39 C) temperatures. The RNA-synthesizing activity of all four ts mutants was more labile at 39 C than was the transcriptive activity of wild-type (wt) virions. In order to locate the temperature-sensitive transcription defect in the mutants, wt and ts mutant virions were fractionated by Triton X-100-high salt solubilizer into a sedimentable ribonucleoprotein template and a nonsedimentable enzyme fraction, each of which alone had little or no transcriptive activity. The template- and enzyme-containing fractions of wt virions were then tested for their capacity to restore transcriptive activity at 39 C to corresponding template and enzyme preparations of ts mutant virions. Recombination of wt template and ts enzymes resulted in no significant restoration of capacity to synthesize RNA at restrictive temperature. In contrast, transcriptive function at 39 C was reconstituted by recombining the wt enzyme with the template component of ts mutants. It appears, therefore, that the enzyme, rather than the template, is the temperature-sensitive component of the transcription complex of group I vesicular stomatitis virus mutants.